2005
DOI: 10.1021/jp0544540
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Size Dependence of Young's Modulus Using Force Modulation Atomic Force Microscopy

Abstract: The dependence of the local Young's modulus of organic thin films on the size of the domains at the nanometer scale is systematically investigated. Using atomic force microscopy (AFM) based imaging and lithography, nanostructures with designed size, shape, and functionality are preengineered, e.g., nanostructures of octadecanethiols inlaid in decanethiol self-assembled monolayers (SAMs). These nanostructures are characterized using AFM, followed by force modulation spectroscopy and microscopy measurements. You… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 70 publications
3
35
1
Order By: Relevance
“…As shown in Figure 4, Young's modulus is 0.1-0.3 GPa under the loaded force. Compared with the previous report on Young's modulus of about 1 GPa for self-assembled thiols [10] , it can be predicted that dsDNA is very soft under the experimental conditions, thus dsDNA is so easy to bend. Furthermore, Young's modulus decreased nonlinearly with increasing loading force.…”
Section: Analytical Chemistrycontrasting
confidence: 78%
See 1 more Smart Citation
“…As shown in Figure 4, Young's modulus is 0.1-0.3 GPa under the loaded force. Compared with the previous report on Young's modulus of about 1 GPa for self-assembled thiols [10] , it can be predicted that dsDNA is very soft under the experimental conditions, thus dsDNA is so easy to bend. Furthermore, Young's modulus decreased nonlinearly with increasing loading force.…”
Section: Analytical Chemistrycontrasting
confidence: 78%
“…Results showed that the reversible deformation of DNA molecules deposited on mica surfaces was able to reach about 50% under external load, with a compression elastic constant of about 0.6 nN/nm. Similar methods have also been applied to other important nanomaterials, such as single-wall carbon nanotubes, cytoskeletal systems, and self-assembled monolayers (SAMs) [9][10][11] . However, there are still many problems pending, including how to deduce the Young's modulus of dsDNA.…”
mentioning
confidence: 99%
“…When the measuring temperature rises, the stress drops and changes from tensile to compressive [212]. However, the Y values for the polymer nanostructures drop with size according to the relation Y ¼ 0.014 ln(x) þ 0.903 AE 0.045 [213], with x being the particle size. The Ysuppression indicates the importance of the (T m ÿ T ) contribution in determining the size effect on mechanical strength.…”
Section: 122mentioning
confidence: 99%
“…Researchers have used the method to study the effect of nanostructure geometry on material stiffness for structures as small as 20 nm at a resolution on the order of 10 MPa. 3 Interfacial properties of the tip-surface junction may be similarly probed with contact-mode techniques by adjusting the position of the cantilever to apply compressive or tensile forces to the sample. Reducing the applied load until the tip disengages from the sample yields the system's interfacial energy, or work of adhesion; the spatial resolution is limited by the contact radius of the junction, typically 1-2 nm.…”
Section: Tip-surface Interactionmentioning
confidence: 99%